Uncertain Environment of Enterprise Alliance in Supply Chain Network Optimization - Sun Qiong; Long Runxiang (Institute of Advanced Engineering and Science, 2014)
According to the actual situation of the enterprise alliance of supply chain networks and considering the complexity of the various links in the supply chain of uncertain factors, it should be take a solution on decomposition strategy - coordination of the supply chain system optimization and focus on the supply cost analysis facility decision on supplier selection and cost, the two a problem of coordination through the integration of activity-based costing. Then establish the supply chain network design of robust model. Finally, using stochastic simulation method and the particle swarm algorithm based on hybrid intelligent algorithm for solving the robust optimal solutions of the model, and an example is used to demonstrate the feasibility and effectiveness of the model and algorithm. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4510